(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The aim was to compare the chemical composition and some properties of three industrial lignosulfonates produced as a by-product at three pulp and paper mills (Russia). Using the classical methods of lignin chemistry, it was found that there were differences in the elemental composition and the content of functional groups of the industrial lignosulfonates, but in general, they were not very significant. The Kondopoga lignosulfonates contained the highest content of methoxy, aliphatic hydroxyl groups and carbonyl groups. The Vyborg lignosulfonates had the highest degree of sulfonation and the lowest content of carbonyl groups. The content of the functional groups in the chemical composition of the Syassky lignosulfonates was intermediate between the functional composition of the Vyborg and Kondopoga lignosulfonates. The Vyborg lignosulfonates had the lowest values of the viscosity average molecular mass, dynamic viscosity and surface tension at the air-water interface in comparison with these parameters of the Kondopoga and Syassky lignosulfonates.